2009
DOI: 10.1074/mcp.m800372-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast Vacuolar Membrane Proteome

Abstract: Transport of solutes between the cytosol and the vacuolar lumen is of crucial importance for various functions of vacuoles, including ion homeostasis; detoxification; storage of different molecules such as amino acids, phosphate, and calcium ions; and proteolysis. To identify proteins that catalyze solute transport across the vacuolar membrane, the membrane proteome of purified Saccharomyces cerevisiae vacuoles was analyzed. Subtractive proteomics was used to distinguish contaminants from true vacuolar protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 70 publications
4
77
0
Order By: Relevance
“…The function of the five other PQ-loop proteins is unknown. At least two of them, Yol092p and Ydr352p (hereafter called Ypq1 and Ypq2), were reported in proteomic and genome-scale protein localization studies to be located at the membrane of the vacuole, the lysosome of yeast (23,24). By colabeling with fluorescent FM4-64 dye, we observed that Ypq1-GFP and Ypq2-GFP fusion proteins are indeed located at the vacuolar membrane and found that the same is true for another member of the family, Ybr147p, hereafter called Ypq3 (Fig.…”
mentioning
confidence: 99%
“…The function of the five other PQ-loop proteins is unknown. At least two of them, Yol092p and Ydr352p (hereafter called Ypq1 and Ypq2), were reported in proteomic and genome-scale protein localization studies to be located at the membrane of the vacuole, the lysosome of yeast (23,24). By colabeling with fluorescent FM4-64 dye, we observed that Ypq1-GFP and Ypq2-GFP fusion proteins are indeed located at the vacuolar membrane and found that the same is true for another member of the family, Ybr147p, hereafter called Ypq3 (Fig.…”
mentioning
confidence: 99%
“…This in vivo interaction did not require aldolase catalytic activity, as mutants lacking the catalytic site were still capable of interacting (Lu et al, 2007), although the exact mechanism of regulation remains unclear, and it has not been related to a specific stress condition. Enolase also appears to bind to yeast vacuoles through a peripheral membrane association, but the target protein on the membrane remains unknown (Decker and Wickner, 2006;Wiederhold et al, 2009). In order to determine if in M. crystallinum these enzymes are associated to the tonoplast by means of physical interaction with subunits of the V-ATPase, we performed reciprocal immunoprecipitation assays on tonoplast isolated from control and salt-treated plants using antibodies against aldolase, enolase, VHA-B, and VHA-E subunits ( Figure 5).…”
Section: Immunoprecipitation Reveals Interaction Between Glycolytic Ementioning
confidence: 99%
“…Because of their subnanometer size, the engineered, drug-carrying vacuoles could rapidly extravasate and accumulate in the periphery of tumor tissue, where, after cancer receptor engagement, they could undergo endocytosis before releasing their payload and producing cytotoxic effects. In addition, with the available rapid protocols for vacuole preparation and methods for large-scale fermentation of yeasts, it is possible to obtain high yields of vacuoles in a cost-effective manner (26,33).…”
Section: Resultsmentioning
confidence: 99%